Insights to plant–microbe interactions provide opportunities to improve resistance breeding against root diseases in grain legumes. (3rd July 2018) - Wille, Lukas; Messmer, Monika M.; Studer, Bruno; Hohmann, Pierre
Abstract: Root and foot diseases severely impede grain legume cultivation worldwide. Breeding lines with resistance against individual pathogens exist, but these resistances are often overcome by the interaction of multiple pathogens in field situations. Novel tools allow to decipher plant–microbiome interactions in unprecedented detail and provide insights into resistance mechanisms that consider both simultaneous attacks of various pathogens and the interplay with beneficial microbes. Although it has become clear that plant‐associated microbes play a key role in plant health, a systematic picture of how and to what extent plants can shape their own detrimental or beneficial microbiome remains to be drawn. There is increasing evidence for the existence of genetic variation in the regulation of plant–microbe interactions that can be exploited by plant breeders. We propose to consider the entire plant holobiont in resistance breeding strategies in order to unravel hidden parts of complex defence mechanisms. This review summarizes (a) the current knowledge of resistance against soil‐borne pathogens in grain legumes, (b) evidence for genetic variation for rhizosphere‐related traits, (c) the role of root exudation in microbe‐mediated disease resistance and elaborates (d) how these traits can be incorporated in resistance breeding programmes. Abstract : This review summarizes increasing evidence on (a) the involvement of the root‐associated microbial community in resistance mechanisms of grain legumes against complex pathogen scenarios in agricultural fields, (b) a plant genetic basis for defence‐related plant‐microbiome interactions, and (c) how these findings can be exploited by breeders towards microbiome‐supported resistance breeding.